The education of Corporal John Musgrave: Vietnam and its aftermath (Alfred A. Knopf, 2021)
Like nearly all the boys he knew, John Musgrave grew up looking forward to the day he could enlist in the Marine Corps and serve his country as his father had done. In this memoir, Musgrave renders his wartime service with intimacy and immediacy: from the rude awakening of boot camp to daily life in the Vietnam jungle to the chest wound that nearly killed him. Musgrave also describes the difficulty of returning home to a society rife with antiwar sentiment his own survivor's guilt, and the slow realization that he and his fellow veterans had been betrayed by the government they served.
Born to Serve , The House of Horrors , Drill Instruction , Finishing School , Shipping Out , First Contact , Joining the Varsity Team , M-I-S-E-RY , Operation Buffalo , The Kill Zone , Leaving the Corps , Big Vet on Campus , Joining the VVAW , Public Speaking , Finding the Others , Epilogue: Coming Full Circle.